The co-articulation of national identity and interculturalism in the Irish curriculum: educating for democratic citizenship?. (1st March 2008) - Bryan, Audrey
Abstract : Article 2008 This article considers social and educational policy responses to increasing ethnic diversity in the Republic of Ireland and related concerns about the intensification of racism in Irish society in the 'Celtic Tiger' era. Drawing on approaches which emphasise the extent to which discourses on 'race' and multiculturalism are woven into a more general concern about the nation, I problematise interculturalism as a policy response to the intensification of racism in Irish society in recent years. Drawing on a corpus of recently published policy documents and curriculum materials currently being used in Irish secondary schools, I argue that racial inequality is more likely to be reproduced, rather than contested, through national and educational policies and practices which are purported to have egalitarian and anti-racist aims. Implications of the study are discussed in terms of alternative approaches to educating for democratic citizenship.